Persekutuan Umat Allah Di Dalam Cyberspace - Thomas Onggo Sumaryanto; Hariawan Adji (Jurnal Teologi Kontekstual Indonesia, 2021)
This research departs from the phenomenon of live streaming mass due to the Covid-19 pandemic. Face-to-face mass activities were eliminated and replaced by using live streaming media. The focus of this research is to see how the value of the communion of people in the Eucharist can be maintained in cyberspace. Researchers used qualitative research methods with a theological reflection approach based on the thoughts of Antonio Spadaro and Anthony Le Duc about cyber theology. The novelty of this research is a theological reflection from the perspective of the teachings of the Catholic Church. The results showed that the people were helped to maintain the value of the Eucharistic communion in the midst of a pandemic. Cyberspace is a forum to strengthen relationships between believers emotionally and spiritually. However, it must be emphasized that cyberspace is only a supplement. This space is needed according to the portion and remains actualized in a real and direct relationship. Research data shows that people feel that they are not enough with live streaming mass. The church needs to help people to reflect more deeply on the relationship between God and humans in cyberspace. Therefore the Church has a tough task after the pandemic ends. AbstrakPenelitian ini berangkat dari fenomen misa live streaming akibat pandemik Covid-19. Kegiatan misa secara tatap muka ditiadakan dan diganti dengan memanfaatkan media live streaming. Fokus penelitian ini melihat bagaimana nilai persekutuan umat di dalam Ekaristi bisa dipertahankan dalam cyberspace. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan refleksi teologis berdasarkan pemikiran Antonio Spadaro dan Anthony Le Duc tentang cybertheology. Kebaruan penelitian ini adalah refleksi teologis dengan sudut pandang ajaran Gereja Katolik. Hasil penelitian menunjukkan bahwa umat dibantu untuk mempertahankan nilai persekutuan Ekaristi di tengah pandemi. Cyberspace menjadi wadah untuk menguatkan relasi antarumat secara emosional dan spiritual. Namun yang harus ditekankan adalah cyberspace hanya suplemen. Ruang ini dibutuhkan sesuai porsinya dan tetap diaktualisasikan dalam relasi nyata dan langsung. Data penelitian menunjukkan umat merasa tidak cukup dengan misa live streaming. Gereja perlu membantu umat untuk merefleksikan lebih mendalam lagi relasi Tuhan dan manusia di dalam cyberspace. Oleh sebab itu Gereja mempunyai tugas berat setelah pandemi berakhir.